2020
DOI: 10.1093/rheumatology/keaa138
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of age and obesity to the number of painful joint sites in individuals reporting osteoarthritis: a population-based study

Abstract: Objective To investigate the association of OA risk factors with number of painful joint sites in a representative population sample. Methods Analysis of the 2009 Survey on Living with Chronic Diseases in Canada – Arthritis Component (n = 1614) for respondents reporting symptomatic OA. Variables: painful joints sites (hands, wrists, elbows, shoulders, hips, knees, ankles, feet, back, neck), joint symptom duration, sociodemogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 46 publications
4
22
0
Order By: Relevance
“…Obesity and OA are two common health problems in the world. The latest research has indicated that obesity affects the occurrence and development of OA [4][5][6][7]. Moreover, it has been revealed that obesity is a risk element for OA, especially in weight-bearing joints [8].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity and OA are two common health problems in the world. The latest research has indicated that obesity affects the occurrence and development of OA [4][5][6][7]. Moreover, it has been revealed that obesity is a risk element for OA, especially in weight-bearing joints [8].…”
Section: Introductionmentioning
confidence: 99%
“…Age and whether individuals suffered from LDH related to the severity of SIJ degeneration. It is well established that age is one of the most critical contributors to the degenerative change in the musculoskeletal system, while it is intriguing that LDH is as important as age in the model (28). Limited studies point out that SIJ degradation is relevant to BMI and gender, but this research did not detect any clue among these issues (12,29).…”
Section: Discussionmentioning
confidence: 55%
“…To investigate the possible impact of OA in other affected joints, we accessed data from the 2009 Survey on Living With Chronic Diseases in Canada, arthritis component (SLCDC‐A), a representative sample of Canadians reporting arthritis. Briefly, the sample for the SLCDC‐A (n = 4,565) was drawn from respondents age ≥20 years in the 2008 Canadian Community Health Survey (CCHS) who reported being told by a health professional that they had arthritis as a long‐term chronic condition (3,34). The SLCDC‐A included questions about pain, aching, or stiffness on most days in the last month due to arthritis at 11 joint sites (shoulder, elbow, wrist, hand/fingers/thumb, hip, knee, ankle, foot/toes, neck, back, and other joint sites) and about the type of their arthritis (3,34).…”
Section: Methodsmentioning
confidence: 99%
“…It is increasingly being recognized that osteoarthritis (OA) is a multi-joint disease. Population-based studies suggest that ≥70% of those affected have symptoms at >1 joint site (1)(2)(3), and clinical studies confirm the frequent co-occurrence of OA at different joint sites (4)(5)(6). However, most epidemiologic and clinical studies are predominantly concerned with OA of the knee, hip, or hand and refer to them as separate conditions, with little or no consideration of OA in other joints (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%